Analysis of Knowledge Management in Information Systems Faculty of Da'wah and Communication Studies UIN Syarif Hidayatullah Jakarta based on Usability Evaluation - Hardi, Tomi (Data Science: Journal of Computing and Applied Informatics, 2020)
Information systems are media used to channel information. each campus has a medium for channeling information. One of them is the UIN Syarif Hidayatullah Jakarta campus. One of the information systems owned by Uin Syarif Hidayatullah Jakrta is the information system at the Faculty of Da'wah and Communication Studies. In this system there are several parts, namely the homepage, accreditation, academic, student affairs, library and others. The purpose of this study is to evaluate Usability to improve user satisfaction in using this information system. The research method used is literature study, field studies and SUMI (Software Usability Measurement Inventory) questionnaire. The questionnaire was conducted on 20 respondents namely 10 lecturers and 10 students of the da'wah and communication faculty. The questionnaire was carried out in 3 categories, namely effectiveness, efficiency and satisfaction with the linker agreed, disagreed and did not know. The results of the SUMI questionnaire calculation of the information system are 80, 75,75,70,70,87.5. The usability evaluation results are above average, meaning that usability in the Da'wah and Communication faculty information system has been going well.